Single-cell atlas of splenocytes reveals a critical role of a novel plasma cell‒specific marker Hspa13 in antibody class-switching recombination and somatic hypermutation. (January 2022) - Zhai, Bing; Liu, Xiaoling; Xu, Yaqi; Zhu, Gaizhi; Zhou, Shan; He, Youdi; Wang, Xiaoqian; Su, Wenting; Han, Gencheng; Wang, Renxi
Highlights: Hspa13 is a novel PC-specific marker. Hspa13 cKO reduced Ebi3 and IL-10 expression in PCs. Hspa13 cKO reduced IL-4-expressing Tfh cells and IL-4 expression. Hspa13 cKO reduced Aicda expression and Aicda -mediated CSR and SHM. Abstract: Our previous study had shown that member 13 (Hspa13) of heat shock protein family A (Hsp70) promotes plasma cell (PC) production and antibody secretion. To further explore Hspa13 expression and function, we combined single-cell RNA-sequencing and antigen receptor lineage (BCR) analysis to characterize sheep red cell‒primed splenocytes. The single-cell transcriptional profiles revealed that Hspa13 is specifically and highly expressed in PCs. These results suggest that Hspa13 is a novel PC-specific marker. In terms of its function, we found that the CD19 cre -mediated conditional knock-out (cKO) of Hspa13 reduced the expression of Ebi3 and IL-10 in PCs. Ebi3 and IL-10 are important factors in IL-4‒secreting type 2 helper T cell (Th2) activation and differentiation. As expected, we found that the Hspa13 cKO reduced IL‒4-expressing follicular helper T (Tfh2) cells. Finally, the single-cell antigen receptor analysis demonstrated that the Hspa13 cKO reduced the Aicda -mediated antibody class-switching recombination (CSR) and somatic hypermutation (SHM) in germinal centers (GCs) B cells. Altogether, the single-cell atlas of splenocytes revealed a critical indirect role for the novel PC-specific marker Hspa13 in CSR and SHM in GC B cells by promoting Ebi3 and IL-10 expression in PCs to induce IL-4-expressing Tfh2 cells. Further exploration of Hspa13 expression and function will provide valuable clues for how to use Hspa13 in the treatment of autoimmune diseases.